2021
DOI: 10.3390/biology10060480
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Aphid—Plant Interactions under Increased Temperature

Abstract: Thermal stress in living organisms causes an imbalance between the processes of creating and neutralizing reactive oxygen species (ROS). The work aims to explain changes in the aphid–host plant interaction due to an increase in temperature. Tests were carried out at three constant temperatures (20, 25, or 28 °C). Firstly, changes in development of Macrosiphum rosae were determined. Secondly, the activity of enzymatic markers (superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), β-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…The populations of the two clones dropped sharply whilst being exposed to the applied heatwave. This resonates with the findings of Chen et al (2000) [44] on a reduced pea aphid fecundity at 25°C, and those of Dampc et al (2021) [45] who found that exposure to 28°C affected the reproduction and longevity of rose aphid Macrosiphum rosae (Linnaeus) by altering plant-aphid interaction and their defence mechanism. Survival and nymph production in the severe condition were higher in N116 than in N127.…”
Section: Discussionsupporting
confidence: 90%
“…The populations of the two clones dropped sharply whilst being exposed to the applied heatwave. This resonates with the findings of Chen et al (2000) [44] on a reduced pea aphid fecundity at 25°C, and those of Dampc et al (2021) [45] who found that exposure to 28°C affected the reproduction and longevity of rose aphid Macrosiphum rosae (Linnaeus) by altering plant-aphid interaction and their defence mechanism. Survival and nymph production in the severe condition were higher in N116 than in N127.…”
Section: Discussionsupporting
confidence: 90%
“…Aphids are oligophagous insects that feed on plants and cause damage to shoots and leaves, making them major pests across several agricultural systems, being also efficient vectors of phytopathogenic viruses (Dampc et al, 2021). As sessile organisms, plants had to evolve ways to defend themselves against herbivores (Walling, 2000), or, when in oligo-cultures, also to develop ways of transmitting signals to each other and use these signals for enhancing collective resistance (Rasmann et al, 2005;Cascone et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The spring phenology of trees is generally defined as a response to effective heat sums [20]. Being ectothermic animals, aphids are strongly affected by thermal conditions [22,23]. Temperature mainly affects the life activities of these insects, influencing the rate of their development, the phenology of appearance, spring and autumn migrations, and the survival of the species [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%